Miscellanea: VIII (Catholic record society, 1914)
Records of the English Benedictine nuns at Cambrai, 1620-1793; adherents of Mary Queen of Scots; Thomas Holland; Courtfield Muniments; Jesuits, 1727-1734; Ralph Clavering; Liege Academy; Roman Catholic Club, 1793-8; Registers in Lancashire, 1713-17; Registers of Danby, West Witton and Leyburn, Yorks; Claxby, Lincs; Oscott, Warwicks; Britwell-Prior, Oxon; Isleworth, Middlesex; Newport, Salop; Culcheth, Lancs; Southworth Hall, Lancs.